'Freedom is more important than health': Thomas Szasz and the problem of paternalism. Issue 2 (May 2014) - Moncrieff, Joanna
Abstract : When Thomas Szasz summed up his philosophical principles at the Royal College of Psychiatrists' annual meeting in Edinburgh in 2010, he declared that 'freedom is more important than health'. Psychiatry is the arena in which the conflict between freedom and health comes most sharply into focus, according to Szasz. This paper proposes some parallels with medicine in low-income countries for pointers towards a resolution of this conflict.